Structural Analysis of the In-Vessel RMP IM-Coils of the TCABR Tokamak - Bouzan, Andre S.; Ramos, Roberto; Salvador, Felipe M.; Elizondo, Juan I.; Saab, Joseph Y.; Bekman, Felipe; Degasperi, Francisco T.; Pauletti, Ruy M. O.; Canal, Gustavo P. (IEEE transactions on plasma science, 2024)
An upgrade of the Tokamak à Chauffage Alfvén Brésilien (TCABR) is being carried out to allow for studies of the impact of resonant magnetic perturbation (RMP) fields on plasma instabilities known as edge localized modes (ELMs). For that, a unique set of RMP coils is being designed and will be installed inside the vacuum vessel. These coils will be subject to extreme conditions: they have to operate with relatively high electric currents ( {≤ }2 kA), voltages ( {≤ }4 kV), temperatures ( {≤ } 200~^{°} \text{C} ), and vacuum ( {≤ } 1\,\,× {}10^{-7} mbar), to withstand strong electromagnetic forces ( {≤ }6 kN) and to be relatively small to fit the reduced space available between the vacuum vessel walls and the graphite protection tiles. This work presents a complete structural analysis of one particular set of these in-vessel coils (the so-called IM-coils) using finite element numerical simulations. The maximum equivalent von-Mises stresses obtained for the proposed mechanical design satisfies both ASME and ITER criteria.